PENGARUH SELF REGULATED LEARNING, GRIT TERHADAP STRES AKADEMIK DALAM PEMBELAJARAN ONLINE DIMASA PANDEMI COVID-19 PADA MAHASISWA DI KOTA PADANG BERBASIS TEKNOLOGI INFORMASI - Ifani Candra; Maha Rani (Program Studi S1 Psikologi, 2022)
The purpose of this study was to determine the effect of self-regulated learning, grit on academic stress in online learning during the COVID-19 pandemic on students in the city of Padang based on information technology. The data collection method used a self-regulated learning scale, grit scale and academic stress scale with sampling techniques using purposive sampling and snowball sampling, a sample of 1130 students in the city of Padang. The data analysis method used is multiple linear regression analysis. Based on the results of the study, it showed that there was a significant and negative effect simultaneously between self-regulated learning, grit on academic stress in online learning during the covid-19 pandemic for students in the city of Padang, as seen from Fhitung 271,660> Ftable 3,00371 the hypothesis was accepted and p=0,000< 0.05, and there is a significant and negative effect between self-regulated learning on academic stress in online learning during the COVID-19 pandemic on students in the city of Padang with thitung 5.777> ttable 1.962071 the hypothesis is accepted with p=0.000<0.05, and there is a significant effect between grit on academic stress in online learning during the covid-19 pandemic on students in the city of Padang as seen from thitung 12.872 > ttable 1.962071 the hypothesis is accepted with p= 0.000<0.05. The results of the coefficient of determination between self-regulated learning, grit on academic stress are 32.4% and 67.6 are influenced by other factors.